Effect of intraocular lens glistening size on visual quality. Issue 6 (June 2015) - Henriksen, Bradley S.; Kinard, Krista; Olson, Randall J.
Abstract : Purpose : To determine whether intraocular glistenings have an impact on light scatter and visual function. Setting : John A. Moran Eye Center Laboratories, University of Utah, Salt Lake City, Utah, USA. Design : Retrospective cohort study. Methods : Pseudophakic patients with visual acuity no worse than 0.02 logMAR and no ocular pathology were enrolled. All had received a single‐piece high‐refractive‐index acrylic intraocular lens (IOL). All IOLs were photographed, and glistenings were analyzed for size and density. Outcome measures included logMAR corrected distance visual acuity (CDVA), mesopic 10% contrast logMAR CDVA with and without glare, and straylight determination with a straylight meter (C Quant log). Results : All 79 patients had glistenings within 2 diameter groups: 6 to 25 μm and over 25 μm. Linear regression for the nonstratified group was significant for IOL glistening size versus contrast visual acuity with glare. Linear regression for the 6 to 25 μm group was significant for a measure of severity index (%area) versus the straylight meter measurements, %area/size versus straylight meter measurements, IOL age versus CDVA, IOL age versus contrast visual acuity, and IOL age versus contrast visual acuity with glare. Linear regression for the over 25 μm group was significant for IOL age versus glistening size and %area/size versus contrast visual acuity, and density versus CDVA and contrast visual acuity with glare. Conclusions : Glistening %area, at a key size, correlated with random light scatter. The age of the IOL likely affects glistening size and visual parameters. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.